Outcomes in Catheter Ablation of Sustained Ventricular Tachycardia in Myocarditis Compared with Ischemic Heart Disease - Sheng Su; Le Li; Xi Peng; Likun Zhou; Zhuxin Zhang; Yulong Xiong; Zhenhao Zhang; Mengtong Xu; Yan Yao (Reviews in Cardiovascular Medicine)
Background: The substrates for arrhythmias in myocarditis and ischemic heart disease (IHD) are different, but it is yet to be determined whether there is a difference in outcomes following catheter ablation (CA) for ventricular tachycardia (VT) associated with these two conditions. This study aimed to compare outcomes after CA of VT in patients with myocarditis versus those with IHD. Methods: Patients undergoing CA for sustained VT confirmed by endomyocardial biopsy as myocarditis, and patients with IHD experiencing sustained VT undergoing CA were retrospectively enrolled from February 2017 to March 2023. Initially, an endocardial approach was employed, reserving epicardial ablation procedures for non-responders. The primary endpoint was VT recurrence during follow up. All-cause mortality, repeat CA for VT and implantable cardioverter-defibrillator (ICD) implantation served as secondary endpoints. Kaplan-Meier curves compared outcomes between patient groups. Results: This study included 109 patients with IHD and 20 patients with myocarditis who underwent CA for sustained VT, from February 2017 to March 2023. Compared with IHD patients, myocarditis patients had a statistically significant lower complete short-term success rate of CA (60.0% vs. 85.3%, p = 0.013). During a follow-up period of 37 ± 21 months, 8 (40.0%) myocarditis patients experienced VT recurrence compared to 57 (52.3%) IHD patients, with no statistically significant difference between the two groups. During follow-up, 2 (10.0%) myocarditis patients died and 2 (10.0%) underwent repeat CA for VT recurrence, while 9 (8.3%) IHD patients died, 14 (12.8%) underwent a second CA for VT recurrence, and 8 (7.3%) received an ICD implantation. Additionally, there were no notable variations between the two groups regarding all-cause mortality, repeat CA for VT and ICD implantation. Conclusions: It was demonstrated that the efficacy of CA in sustained VT in myocarditis patients was similar to that in IHD. For myocarditis patients with VT, CA might be equally effective.